“Islamization of Knowledge” Seminar Held at the Institute of Education, London University (American Journal of Islam and Society, 1987)
The seminar which was held on October 31, 1987 was aimed at introducingthe International Institute of Islamic Thought (IIIT) to the Muslim intellectualsin the United Kingdom. The seminar was attended by over 40 peopleof different specializations from various parts of the United Kingdom. Theseminar was divided in two sessions. The morning session was chaired byDr. Tayyib Zain al-Abidin, the representative of the Institute in Khartoum,Sudan. The speakers in this session included: Dr. ‘AbdulHamid AbuSulayman,Director General, IIIT; Mr. Mashuq Aly, Head of the Department of IslamicStudies, Lampeter University College, Wales; and Dr. Salim Al-Hasani, Man-Chester University.Dr. AbdulHamidd AbuSulayman outlined the objectives and goals of theInstitute and clarified the concept of the Islamization of Knowledge which,according to him, constituted the very raison detre of the Institute. He emphasizedthat the Muslim world lacked neither resources nor values; whatit lacked was the correct methodology of thinking in order to tackle the pressingproblems of today. The problem, therefore, is primarily a problem of thought.It is incumbent upon the Ummah to reform its methodology of thinking andof solving its problems.Dr. AbuSulayman then traced the developments that led to the establishmentof the Institute. He explained that through their work in student organizations,he and his colleagues arrived at the conclusion that political and socialwork was not enough and that there was a need for work in the field of thoughtand intellectual analysis. It was also not enough to criticise and express dismayat the present bad conditions of the Ummah. What was needed was to presentan alternative Islamic paradigm of intellectual thought and practical solutionsof the problems of the Islamic world.It was therefore decided to establish the Association of Muslim Social Scientists(AMSS) in the United States of America. Building on the experiencegained in the AMSS, the International Institute of Islamic thought was establishedas an independent organization to deal with the problem of intellectual ...